Antibacterial and Antibiofilm Activity of Katuk Leaf Fraction (Sauropus androgynus (L.) Merr.) against Bacteria Staphylococcus Aureus ATCC 25923 - Khairunnisa, Rizky Dila; Sunarni, Titik; Saptarini, Opstaria (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine the antibacterial and antibiofilm activity of extracts and fractions from katuk leaves against Staphylococcus aureus. Katuk leaves were extracted using the maceration process and fractionated using the liquid-liquid method with solvents such as n-hexane, ethyl acetate, and water. Diffusion and dilution methods were used to measure the antibacterial activity, and crystal violet staining at a wavelength of 595 nm was used to measure the inhibition and biofilm destruction activities. The antibacterial and antibiofilm test results obtained were analyzed using ANOVA statistical test. The results of the diameter of the inhibition zone with a concentration of 75 mg/ml showed that the extract was 11.3 ± 1.02 mm, the ethyl acetate fraction was 18.1 ± 2.46 while the water and n-hexane fractions were 0.0 ± 0.0 mm. The antibiofilm test results showed inhibitory activity against Staphylococcus aureus bacteria with the average IC50 values obtained from extracts, n-hexane, ethyl acetate, and water fractions were 10.248±0.405; 11.799±0.355; 8.332±0.585; and 11.372±0.557. While the average EC50 values obtained from the extract, n-hexane, ethyl acetate, and water fractions were 9.343±0.586; 10.530±0.483; 7.695±0.491; and 8.490±0.954.